2015
DOI: 10.1210/en.2015-1068
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting PC1/3 Mutants: Dominant-Negative Effect of Endoplasmic Reticulum-Retained Mutants

Abstract: Prohormone convertase 1/3 (PC1/3), encoded by the gene PCSK1, is critical for peptide hormone synthesis. An increasing number of studies have shown that inactivating mutations in PCSK1 are correlated with endocrine pathologies ranging from intestinal dysfunction to morbid obesity, whereas the common nonsynonymous polymorphisms rs6232 (N221D) and rs6234-rs6235 (Q665E-S690T) are highly associated with obesity risk. In this report, we revisited the biochemical and cellular properties of PC1/3 variants in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 51 publications
(94 reference statements)
3
30
0
Order By: Relevance
“…Creemers et al proposed that mutations in close proximity of this calcium-binding site could alter enzyme stability which could lead to protein misfolding and thereby decreasing the amount of active enzyme (73). Recent evidence from our group and the Lindberg group confirmed that some PCSK1 mutations lead to protein instability (89,205). In particular, our results indicate that several of the identified heterozygous mutations caused a delayed exit of the mutant protein from the cell (205).…”
Section: Functional Consequences Of Human Pcsk1 Variants: Hints Fsupporting
confidence: 61%
See 4 more Smart Citations
“…Creemers et al proposed that mutations in close proximity of this calcium-binding site could alter enzyme stability which could lead to protein misfolding and thereby decreasing the amount of active enzyme (73). Recent evidence from our group and the Lindberg group confirmed that some PCSK1 mutations lead to protein instability (89,205). In particular, our results indicate that several of the identified heterozygous mutations caused a delayed exit of the mutant protein from the cell (205).…”
Section: Functional Consequences Of Human Pcsk1 Variants: Hints Fsupporting
confidence: 61%
“…As described above, the inhibitory function of PC1/3 prodomain was already established in vitro (54,56,57). The earlier described PCSK1-p.G209R mutant which was shown to retain the PCSK1-p.P258T hypomorph in the ER, could have a similar limited dominant negative effect (89). Aside from a clear relation with increased BMI in the reported patients, it remains unclear whether heterozygosity can lead to other endocrinopathies which are reported for null patients.…”
Section: B Heterozygous Mutations Contribute To Obesitymentioning
confidence: 77%
See 3 more Smart Citations